Clinical and Radiographic Outcomes of Midfoot Arthrodesis Using Different Fixation Methods. Issue 3 (14th September 2018) - Bejarano-Pineda, Lorena; Huh, Jeannie; DeOrio, James; Lampley, Alexander; Easley, Mark
Category: Midfoot/Forefoot Introduction/Purpose: Midfoot arthritis is a disabling condition, causing chronic foot pain and functional disability. The goals of midfoot arthrodesis are to a plantigrade, stable, and pain-free foot. The procedure can be technically demanding and associated with a number of complications. The use of midfoot-specific plate fixation has become more popular as an alternative to screw-only fixation. The purpose of this study was to compare the clinical and radiographic outcomes following midfoot arthrodesis using different fixation methods. Methods: This was a retrospective study of all midfoot arthrodeses performed at a single institution between January 2005 and December 2014. Patients qualified if they had a minimum of 12 months follow-up, specifically with patient-reported outcomes. Demographic and surgical information were collected. Final post-operative outcomes were reviewed and consisted of patient-reported functional measures, union rate, complications, and radiographic outcomes. Patient-reported functional measures included the American Orthopedic Foot and Ankle Score (AOFAS) midfoot scale, Visual Analogue Scale (VAS) for pain, and Lower Extremity Functional Score (LEFS). Radiographic outcomes included alignment in the antero-posterior (AP) and lateral views, as measured by the talo-first metatarsal angle during the pre-operative and final follow-up visits. Outcomes were compared among the following groups: Screw fixation group (SFG), plate fixation group (PFG), and combined fixation group (CFG), which had screw and plate fixation. Results: A total of 79 midfoot fusions in 75 patients had a mean follow-up of 61 months (range 13-122) with patient-reported outcome measures. At final follow-up, the SFG had a higher median LEFS (72.5 versus 53 in the PFG and 56 in the CFG; p>0.1) and a higher mean AOFAS score (87 versus 78 in the PFG and 77 in the CFG; p>0.15). The complication and nonunion rate was highest in the PFG, with 13 (50%) and 4 (50%) cases, respectively; however, the differences were not statistically significant. The talo-first metatarsal angle improved in all three groups from a median of 6.4 degrees pre-operatively to 3.9 degrees on final post-operative imaging. Conclusion: Although not statistically significant, there was a trend towards higher patient-reported outcomes, union rate, and less complication rate in midfoot fusions treated with screw fixation compared to plate fixation and combined fixation. There was no difference in radiographic correction among the difference fixation methods. Although new techniques and implants continue to be introduced, we found no significant difference in outcomes when compared to the traditional technique of screw fixation.